2020
DOI: 10.3390/d12090361
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Andean Gymnophthalmid Lizard (Squamata: Gymnophthalmidae) from the Peruvian Andes, and Resolution of Some Taxonomic Problems

Abstract: The family Gymnophthalmidae is one of the most speciose lineages of lizards in the Neotropical region. Despite recent phylogenetic studies, the species diversity of this family is unknown and thus, its phylogenetic relationships remain unclear and its taxonomy unstable. We analyzed four mitochondrial (12S, 16S, Cytb, ND4) and one nuclear (c-mos) DNA sequences of Pholidobolus anomalus, Cercosaura manicata boliviana and Cercosaura sp., using the maximum likelihood method to give insights into the phylogenetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The result of our ML tree is congruent with recent studies [2,11,13,15,53], with some differences, such as the polyphyly of Oreosaurus, Proctoporus iridescens, P. guentheri, and P. spinalis. The topologies of Torres-Carvajal et al [11] and Vásquez-Restrepo et al [14] recovered the polyphyly of Proctoporus, in contrast to topologies of Goicoechea et al [2], Moravec et al [13], and Mamani et al [15], who reported the monophyly of Proctoporus. These contrasting result and low support values do not support the monophyly of Proctoporus.…”
Section: Discussionsupporting
confidence: 91%
“…The result of our ML tree is congruent with recent studies [2,11,13,15,53], with some differences, such as the polyphyly of Oreosaurus, Proctoporus iridescens, P. guentheri, and P. spinalis. The topologies of Torres-Carvajal et al [11] and Vásquez-Restrepo et al [14] recovered the polyphyly of Proctoporus, in contrast to topologies of Goicoechea et al [2], Moravec et al [13], and Mamani et al [15], who reported the monophyly of Proctoporus. These contrasting result and low support values do not support the monophyly of Proctoporus.…”
Section: Discussionsupporting
confidence: 91%
“…However, developing a sound taxonomy depends on complete sampling and the use of powerful analysis methods. In recent years, with broad sampling, application of integrative methods, as well as robust analysis methods, some systematic issues had been well resolved (e.g., Fouquet et al, 2022;Garg & Biju, 2021;Guo et al, 2014Guo et al, , 2019Hou et al, 2021;Liu et al, 2021;Mallik et al, 2020Mallik et al, , 2021Mamani et al, 2020;Sturaro et al, 2018;Vijayakumar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gymnophthalmidae is subdivided into subfamilies-sometimes considered as tribes (Pellegrino et al 2001;Goicoechea et al 2016)-of which Cercosaurinae is the most species-rich, with about half of all recognized gymnophthalmid species. Currently, the more than 150 Cercosaurinae species are grouped in 21 genera (Torres-Carvajal et al 2016;Moravec et al 2018;Sánchez-Pacheco et al 2018;Lehr et al 2019Lehr et al , 2020Fang et al 2020;Mamani et al 2020;Parra et al 2020;Torres-Carvajal et al 2020;Vásquez-Restrepo et al 2020). within this rich subfamily, some linages have evolved a striking phenotype, presumably adapted to aquatic or semi-aquatic life.…”
Section: Introductionmentioning
confidence: 99%